Development of an instructional process based on Ennis approach and peer coaching technique to enhance critical thinking ability - Rajabhat Unversity students - Wongsa, Bencha; Dachakupt, Pimpun; Sakolrak, Soison (2010)
This paper was aimed to develop an education innovation for enhancing critical thinking ability of teacher student at the undergraduate level of Rajabhat University. The developed innovation based in Ennis’s critical thinking approach and peer coaching technique. The objectives of this research were to (1) develop learning process by using Ennis’s critical thinking approach and peer coaching technique so as to accelerate critical thinking ability of Rajabhat University students (2) evaluate the quality of learning process developed.There were 2 key stages of learning process developed h i.e. (1) preparation stage and (2) thinking stage. The second stage, thinking stage, was composed of 5 steps, which were 1)problem structuring of situation, 2) logics and problem scrutiny, 3) thinking summary, 4)understanding manipulation and option selection, and 5) decision making level. The learning process was on process of implementing in classrooms of process and experimental group. The population was undergraduate students of Rajabhat University involved with educational major of teacher professional career. The data were collected by using developed pre-post testing thinking competencies measurement application form of the critical thinking in which was accumulated with “Cornell Critical Thinking Test Level Z” from Ennis and Millman approach and then the data were analyzed by using t-test.